Synthesis of 9-(4-Methoxyphenyl)-3,3,6,6-tetra-3,4,5,6,7,9- hexahydro-2H-xantene-1 using Lime and Lemon Juice as the Environmentally Friendly Catalyst and Its Antioxidant Activity - Rini Retnosari; Nurul Ultiyati; Aman Santoso; Siti Marfu'ah; Ihsan Budi Rachman (Jurnal Kimia dan Kemasan, 2021)
The 9-(4-Methoxyphenyl)-3,3,6,6-tetra-3,4,5,6,7,9-hexahydro-2H-xantene-1 compound, which is addressed as compound 1 in this study, is the derivatives of 1,8-dioxo- octahydroxantene. This compound has a carbonyl group and double bond on beta carbon toward the carbonyl group and benzene ring. The presence of this chromophore helps the compound creates intermediate stabilized by resonance from its interaction with free radicals and has the potential to be an antioxidant. Compound 1 was synthesized from p- methoxybenzaldehyde and dimedone through Knoevenagel condensation reaction using an acid as catalyst. The lime and lemon juice was selected as a catalyst to support green chemistry principle. The obtained product includes white powder with a melting point of 222-224oC. The IR analysis results, GC-MS, and 1H-NMR data show that the compound structure of Compound 1. Meanwhile, the antioxidant activity test using the DPPH method reveal that Compound 1 has the antioxidant activity with IC50 of 22.74 ppm.